Nase zkusenosti s transplantacemi srdce - Hejnal, J; Málek, I; Firt, P; Pirk, J; Kocandrle, V; Straka, F (Rozhledy v chirurgii, 1992)
During the period from 1984-1991 in the Institute of Clinical and Experimental Medicine 72 orthotopic transplantations of the heart were performed in 71 patients with irreversible cardiac failure. Indication for transplantation in 39 patients was IHD, in 28 cardiomyopathy, in 3 RHD and in one instance a tumour. The mean age of the patients was 41 years, the youngest patient was 17 and the oldest 62 years old. Immunosuppression involved a combination of three preparations Azathioprine, corticoids and Cyclosporine A. Nineteen patients died within one month after operation. The most frequent cause of death was cardiac failure. As to postoperative complications, renal failure was most frequent. Fifty patients were followed-up on a long-term basis. The longest survival period was 8 years and 2 months. The most frequent cause of death in the long-term follow-up was sudden death caused in the majority most probably by rapid development of coronary disease.
Keywords: Female; Adult; dospělí; Humans; ženské pohlaví; mužské pohlaví; Male; lidé; transplantace srdce; lidé středního věku; Heart Transplantation; Middle Aged; Adolescent; mladiství